2010
DOI: 10.1093/brain/awq200
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of metabolic brain damage and recovery following mild traumatic brain injury: a multicentre, proton magnetic resonance spectroscopic study in concussed patients

Abstract: Concussive head injury opens a temporary window of brain vulnerability due to the impairment of cellular energetic metabolism. As experimentally demonstrated, a second mild injury occurring during this period can lead to severe brain damage, a condition clinically described as the second impact syndrome. To corroborate the validity of proton magnetic resonance spectroscopy in monitoring cerebral metabolic changes following mild traumatic brain injury, apart from the magnetic field strength (1.5 or 3.0 T) and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
238
3
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 348 publications
(257 citation statements)
references
References 56 publications
12
238
3
4
Order By: Relevance
“…26,27 Significantly, we observed that the recovery of brain metabolism occurred weeks after the resolution of the self-reported postconcussive clinical symptoms. 26,27 Recently, two 1 H MRS studies reported that Cr but not NAA levels were affected by mTBI, with head injury producing a significant increase in Cr levels in different brain areas. 28,29 As indicated earlier, in our previous studies, to investigate possible changes in NAA evaluated relatively to Cr and/or Cho, we excluded patients in whom the Cho/Cr ratio did not remain unaltered.…”
mentioning
confidence: 70%
See 3 more Smart Citations
“…26,27 Significantly, we observed that the recovery of brain metabolism occurred weeks after the resolution of the self-reported postconcussive clinical symptoms. 26,27 Recently, two 1 H MRS studies reported that Cr but not NAA levels were affected by mTBI, with head injury producing a significant increase in Cr levels in different brain areas. 28,29 As indicated earlier, in our previous studies, to investigate possible changes in NAA evaluated relatively to Cr and/or Cho, we excluded patients in whom the Cho/Cr ratio did not remain unaltered.…”
mentioning
confidence: 70%
“…In addition, in our previous article, data obtained from different neuroradiological centers and using the single-or multivoxel technique gave overlapping values. 27 In follow-up studies, the exact repositioning of the voxel on the same acquisition plane obtained in the previous MRI study was achieved by using dedicated software (SameScan; Philips Medical Systems, Philips Healthcare, Best, The Netherlands). Postprocessing of spectral data allowed us to calculate the area under the peaks of NAA, Cho, and Cr, using common criteria for peak integration.…”
Section: Mri and 1 H Mrs Acquisition Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…While up to 90% of concussions resolve in 7–10 days, recovery time may be longer 2. The time to recover may reflect the extent of microscopic neuronal shearing3 and the impairment of cellular and metabolic function 4, 5. While these insights help elucidate the neurophysiology of acute concussive injuries, chronic concussion is still poorly understood and mechanisms explaining the neurobiology over a protracted time scale have not been well characterized.…”
Section: Introductionmentioning
confidence: 99%